Level of Serum C-Reactive Protein (CRP) and Procalcitonin in Non-Alcoholic Fatty Liver Disease Patients (Medical Forum Monthly, 2023)
Objective: To compare the CRP and PCT serum levels in patients with non-alcoholic fatty liver disease (NAFLD) and determine the discriminative and diagnostic role of CRP and PCT.Study Design: Comparative studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Rehman Medical Institute, Peshawar, Pakistan from 1st January 2021 to 31st November 2021.Materials and Methods: Fifty-five patients were taken as study group and fifty-five healthy individuals were taken as control. Body mass index, liver function tests along with insulin resistance was determined. Ultrasound evaluations followed by measuring serum CRP levels with nephelometric method and PCT level measurement by Kryptor based system.Results: There was no difference in the levels of serum PCT in steatohepatitis and simple steatosis patients. CRP levels were found to be higher in steatohepatitis groups as compared with the control group.Conclusion: Serum PCT levels have no diagnostic value and levels of CRP in NAFLD patients were elevated as compared to the control healthy patients’ group. Hence, C-reactive protein can be used as a diagnosing marker for NAFLD but cannot differentiate between simple steatosis and steatohepatitis.